Risk and non-risk based capitalization effect on performance of listed insurers in Nigeria - Sunday, Akpan Sunday (2018)
Financial theories and past researches consider a firm’s capital structure as comprising debt and equity. However, insurers’ capital structure is different; it comprises equity and technical provisions. Particularly, the dynamic tradeoff theory explains the speed of adjustment (SoA) to target capital and associated behavior of firms at trading off irrelevant costs to improve performance. Empirical studies that test this theoretic prediction under different policy regimes within insurance firms are scarce. Risk capital theory says firms that are vulnerable to bankruptcy should hold high capital to be solvent, an idea behind risk based capital (RBC) policy implementation; this seems to have received little empirical attention. Moreover, due to contradictions in past empirical findings, researchers have suggested that the effect of RBC should further be investigated with latent variables as intervening in capital-performance nexus. To date, there is doubt on any existing empirical work in this area. This study was thus conducted to shed these research gaps by examining the direct and indirect effect of capital structure on insurers’ performance with corporate risk profile (CRP) as a moderator comparatively during non-RBC (NRBC) and RBC regimes in Nigeria. It also compares and statistically tests if insurers’ performance during RBC and NRBC era is significantly different. To achieve these objectives, direct and indirect 2SLS FE and RE models were applied. It tests the effect of capital structure (measured by equity ratio -EQR and technical provision ratio –TPR) on insurers’ performance (measured by return on assets - ROA, return on equity – ROE, and earnings per share - EPS) with CRP (measured by opportunity asset risk - OAR and corporate risk-taking behaviour - CRB) as moderating variables. Also, dependent sample and Wilcoxon signed-rank ttest statistics were applied to analyze insurers’ ROA, ROE, and EPS before and after RBC policy implementation. Fifteen (15) listed insurers in Nigeria were studied eight years (1995-2002) before and eight years (2008–2015) after RBC policy implementation. Empirical results of the direct effect model reveal, in general, that TPR affects insurers’ performance significantly and positively than equity in NRBC than in RBC era; equity had a significant positive effect on ROA and EPS, but a significant negative effect on ROE in RBC regime. The indirect effect models reveal generally that, CRP does not moderate insurers’ capital structure and performance association; meaning that insurers do not take high risk, especially during RBC regime. The last model reveals that insurers’ performance significantly reduced after RBC policy implementation. Based on these empirical results, this study has demonstrates that RBC does not improve insurers’ performance; and that, insurers’ risk-taking preferences do not explain their performance beyond the level explained by their financing mix. The theoretical argument is that RBC may not be a bad policy; rather, the manner and strategy of implementation may be inappropriate. Therefore, there is need for strategic policy review to incorporate performance risks, while insurers should focus their strategies on which fund to use for which type of risk to take in RBC scenario to satisfy the interest of all stakeholder.